2001
DOI: 10.1001/archotol.127.8.913
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Gene for Familial Laryngeal Abductor Paralysis to Chromosome 6q16

Abstract: An autosomal dominant form of familial laryngeal abductor paralysis is linked to a 5-centiray region on chromosome 6q16 surrounding D6S1021.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…This was studied and later confirmed by Brunner et al in 1982 [2]. In 2001, a genome linkage analysis identified a locus for familial vocal cord paralysis on the q16 arm of chromosome 6 [13]. Grundfast and Milmoe found bilateral paralysis and swallowing difficulty in a father and his son and daughter.…”
Section: Discussionmentioning
confidence: 82%
“…This was studied and later confirmed by Brunner et al in 1982 [2]. In 2001, a genome linkage analysis identified a locus for familial vocal cord paralysis on the q16 arm of chromosome 6 [13]. Grundfast and Milmoe found bilateral paralysis and swallowing difficulty in a father and his son and daughter.…”
Section: Discussionmentioning
confidence: 82%
“…Manaligod et al described a family with inherited neonatal vocal fold paralysis and used linkage analysis to determine that the abnormality in question mapped to chromosome 6q16 with an autosomal recessive inheritance pattern [11]. Peterson et al found a duplication anomaly at 17q23 associated with the TBX4 gene, a limb development transcription factor [12].…”
Section: Discussionmentioning
confidence: 99%
“…Its inheritance pattern may be autosomal dominant, autosomal recessive or X-linked [8][9][10][11][12][13]. Responsible genes have been localized at chromosomes 6 and 13 [10,12].…”
Section: Discussionmentioning
confidence: 99%
“…Its inheritance pattern may be autosomal dominant, autosomal recessive or X-linked [8][9][10][11][12][13]. Responsible genes have been localized at chromosomes 6 and 13 [10,12]. In non-syndromic cases of congenital bilateral vocal cord paralysis the severity of the obstruction varies, a fair number of infants can be managed conservatively, and the outcome, even in children who needed a tracheotomy, is often favorable in a few years [14].…”
Section: Discussionmentioning
confidence: 99%